DESIGN OF MENTAL HEALTH CENTER WITH BIOPHILIC ARCHITECTURE APPROACH IN MEDAN CITY - Puren, Nursalsabila; Eddy, Firman; Abdillah, Wahyu (Talenta Publisher, 2021)
Indonesia is one of the countries that will enter the era of demographic bonus. The demographic bonus is that the productive age population's growth is more significant than the structure of the unproductive age population. Meanwhile, Indonesia is still experiencing difficulties in one of the health problems often experienced by adolescents, namely mental health. Medan is the capital city of North Sumatra Province, which has the 8th largest depression sufferer. A design approach that can answer this question is biophilic design. Biophilic design is a design approach based on biophilia, which is intended to create a space that can improve the well-being of human life physically and mentally by approaching the positive relationship between humans and nature. The Mental Health Center design method uses qualitative research methods, which will go through several processes that aim to identify the biophilic design and compare it to the interior design facility standards. Â